Gene expression changes in medical workers exposed to radiation - Morandi, Elena; Severini, Cinzia; Quercioli, Daniele; Perdichizzi, Stefania; Mascolo, Maria Grazia; Horn, Wolfango; Vaccari, Monica; Nucci, Maria Concetta; Lodi, Vittorio; Violante, Francesco Saverio; Bolognesi, Claudia; Grilli, Sandro; et al. (Radiation research, 2009)
The use of nuclear resources for medical purposes causes considerable concern about occupational exposure. Nevertheless, little information is available regarding the effects of low-dose irradiations protracted over time. We used oligomicroarrays to identify the genes that are transcriptionally regulated by persistent exposure to extremely low doses of ionizing radiation in 28 exposed professionals (mean cumulative effective dose +/- SD, 19 +/- 38 mSv) compared with a matched sample of nonexposed subjects. We identified 256 modulated genes from peripheral blood mononuclear cells profiles, and the main biological processes we found were DNA packaging and mitochondrial electron transport NADH to ubiquinone. Next we investigated whether a different pattern existed when only 22 exposed subjects with accumulated doses >2.5 mSv, a threshold corresponding to the natural background radiation in Italy per year, and mean equal to 25 +/- 41 mSv were used. In addition to DNA packaging and NADH dehydrogenase function, the analysis of the higher-exposed subgroup revealed a significant modulation of ion homeostasis and programmed cell death as well. The changes in gene expression that we found suggest different mechanisms from those involved in high-dose studies that may help to define new biomarkers of radiation exposure for accumulated doses below 25 mSv.